2020
DOI: 10.3390/molecules25030512
|View full text |Cite
|
Sign up to set email alerts
|

A Non-Targeted Capillary Electrophoresis-Mass Spectrometry Strategy to Study Metabolic Differences in an In Vitro Model of High-Glucose Induced Changes in Human Proximal Tubular HK-2 Cells

Abstract: Diabetic nephropathy is characterized by the chronic loss of kidney function due to high glucose renal levels. HK-2 proximal tubular cells are good candidates to study this disease. The aim of this work was to study an in vitro model of high glucose-induced metabolic alterations in HK-2 cells to contribute to the pathogenesis of this diabetic complication. An untargeted metabolomics strategy based on CE-MS was developed to find metabolites affected under high glucose conditions. Intracellular and extracellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Proximal renal tubules are the main driving force of renal pathology in DM [22]. Therefore, HK2 cell line is a good candidate for studying how high glucose induction promotes the occurrence and progression of DN [23]. Growing evidence suggested that the pathogenesis of DN is related to dysfunction of renal proximal tubular epithelial cell, oxidative stress, inflammation, and fibrosis under a high-glucose condition [24].…”
Section: Discussionmentioning
confidence: 99%
“…Proximal renal tubules are the main driving force of renal pathology in DM [22]. Therefore, HK2 cell line is a good candidate for studying how high glucose induction promotes the occurrence and progression of DN [23]. Growing evidence suggested that the pathogenesis of DN is related to dysfunction of renal proximal tubular epithelial cell, oxidative stress, inflammation, and fibrosis under a high-glucose condition [24].…”
Section: Discussionmentioning
confidence: 99%
“…The effects of a high glucose environment on metabolome have been previously reported for cell lines from pancreas (BRIN-BD11 and INS-1E), [27] liver (HepG2) [28] and kidneys (HK-2). [29][30][31] In the studies mentioned, 25 mM was the maximum concentration of glucose employed to treat the cells, respect to a physiological glucose concentration equal to 5.5 mM. [32] Due to the serious neurological complications associated with pathologies as diabetes, we propose here the HN9.10e hippocampal neuroblasts as model line to study hyperglycemia metabolic effects.…”
Section: Discussionmentioning
confidence: 99%
“…For subsequent studies, HK-2 cells were divided into these groups as needed: control group (HK-2 cells were treated with 5.5 mmol/L D-glucose [G8150; Solarbio, China] for 48 h), osmotic control (Os-control) group (HK-2 cells were treated with 5.5 mmol/L D-glucose and 19.5 mM mannitol (SM8120; Solarbio) for 48 h) [21], PIC-H group (HK-2 cells were treated with 20 μmol/L PIC [SP9130; Solarbio, China] for 24 h, and 5.5 mmol/L D-glucose for 48 h), HG group (HK-2 cells were treated with 30 mmol/L D-glucose for 48 h), HG+PIC-L group (HK-2 cells were first treated with 10 μmol/L PIC for 24 h and then with 30 mmol/L D-glucose for 48 h), and HG+PIC-H group (HK-2 cells were treated with 20 μmol/L PIC for 24 h and 30 mmol/L D-glucose for 48 h).…”
Section: Methodsmentioning
confidence: 99%